ANALISA FAKTOR-FAKTOR YANG TURUT MEMPENGARUHI PERILAKU NASABAH DALAM MENGGUNAKAN KARTU DEBIT - Hati, Shinta Wahyu (IQTISHODUNA, 2009)
In financial service business banking is help people to make manage their properties, especially money, this is support by healthy and prudential banking to growing peopleâ€™s trust. This research has purposed to find to what kind of factors impacts customers use debt card, itâ€™s a shopping style as an alternative payment another credit card. But there are factors impacts customers use debt card are personal factors including of income and education, reference factors including of family and friends advices (social), psychology factors including advertising, and prize, technology factors including faster transaction, more safety, and on line facilities, and dominant factors to affect customers use debt card those factors are the hypothesis in this research.This field research put 65 bank customer use debt card with purposive sampling, this research use Structural Equation Modelling analysis and the result of this analysis there are two factors to attentioned by customer use debt card are personal factors and psychology factors as the dominant decision factors make customers to use debt card.Â